2004
DOI: 10.1523/jneurosci.2724-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

TheDrosophilaMetabotropic Glutamate Receptor DmGluRA Regulates Activity-Dependent Synaptic Facilitation and Fine Synaptic Morphology

Abstract: In vertebrates, several groups of metabotropic glutamate receptors (mGluRs) are known to modulate synaptic properties. In contrast, the Drosophila genome encodes a single functional mGluR (DmGluRA), an ortholog of vertebrate group II mGluRs, greatly expediting the functional characterization of mGluR-mediated signaling in the nervous system. We show here that DmGluRA is expressed at the glutamatergic neuromuscular junction (NMJ), localized in periactive zones of presynaptic boutons but excluded from active sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
141
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(150 citation statements)
references
References 67 publications
8
141
0
Order By: Relevance
“…Flies carrying the DFak CG1 deletion mutation and UAS-DFak 1 transgene (Grabbe et al 2004) were provided by Ruth Palmer (Umeå University, Umeå, Sweden). Flies carrying the DmGluRA 112b deletion mutation (Bogdanik et al 2004) were provided by Marie-Laure Parmentier (Unité Propre de Recherche Centre, Montpellier, France). All other fly stocks were provided by the Drosophila Stock Center (Bloomington, IN).…”
Section: Drosophila Stocksmentioning
confidence: 99%
See 4 more Smart Citations
“…Flies carrying the DFak CG1 deletion mutation and UAS-DFak 1 transgene (Grabbe et al 2004) were provided by Ruth Palmer (Umeå University, Umeå, Sweden). Flies carrying the DmGluRA 112b deletion mutation (Bogdanik et al 2004) were provided by Marie-Laure Parmentier (Unité Propre de Recherche Centre, Montpellier, France). All other fly stocks were provided by the Drosophila Stock Center (Bloomington, IN).…”
Section: Drosophila Stocksmentioning
confidence: 99%
“…In Drosophila, the DmGluRA 112b null mutation in the single mGluR increases motor neuron excitability by preventing activation of the lipid kinase PI3K (Bogdanik et al 2004;Howlett et al 2008). Given that glutamate is the major excitatory neurotransmitter at NMJs in insects such as Drosophila (Jan and Jan 1976), it was suggested that DmGluRA in motor neurons participate in a negative feedback: glutamate released from motor nerve terminals as a consequence of neuronal activity activates DmGluRA autoreceptors in motor nerve terminals.…”
Section: Camkii Regulates Pi3k Activity In Drosophila Motor Nerve Termentioning
confidence: 99%
See 3 more Smart Citations